2020
DOI: 10.1038/s41467-020-16939-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated mRNA decay factor UPF1 promotes aggresome formation

Abstract: Nonsense-mediated mRNA decay (NMD) typifies an mRNA surveillance pathway. Because NMD necessitates a translation event to recognize a premature termination codon on mRNAs, truncated misfolded polypeptides (NMD-polypeptides) could potentially be generated from NMD substrates as byproducts. Here, we show that when the ubiquitin–proteasome system is overwhelmed, various misfolded polypeptides including NMD-polypeptides accumulate in the aggresome: a perinuclear nonmembranous compartment eventually cleared by auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 66 publications
(131 reference statements)
0
27
0
Order By: Relevance
“…Second, UPF1 acts as an E3 ligase to degrade target proteins in an NMD-independent manner [68]. Third, UPF1 senses the CED complex associated with misfolded polypeptides, and guides it to move toward the aggresome in an NMD-independent manner [76]. Thus, UPF1 ensures proper gene expression and protects the cells against the accumulation of misfolded polypeptides (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, UPF1 acts as an E3 ligase to degrade target proteins in an NMD-independent manner [68]. Third, UPF1 senses the CED complex associated with misfolded polypeptides, and guides it to move toward the aggresome in an NMD-independent manner [76]. Thus, UPF1 ensures proper gene expression and protects the cells against the accumulation of misfolded polypeptides (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…As PTC-containing mRNAs targeted for NMD always generate truncated nascent polypeptides (PTC-polypeptides) as byproducts [57,97], such potentially misfolded polypeptides can be transported toward the aggresome upon UPS impairment. Indeed, a recent study showed that PTC-polypeptides generated from a reporter NMD substrate (glutathione peroxidase 1 mRNA harboring a PTC) are enriched in aggresomes after treating cells with MG132, a potent proteasome inhibitor [76]. This observation suggested a possible crosstalk between the NMD pathway and aggresome formation.…”
Section: Upf1 As An Aggresomal Targeting Factormentioning
confidence: 99%
See 2 more Smart Citations
“…4B). P-bodies are conserved ribonucleoprotein granules that contain translationally repressed mRNAs, and mRNA decay factors including proteins involved in NMD (20,39).…”
Section: The Core Nmd Proteins Co-immunoprecipitate In P Falciparummentioning
confidence: 99%